Association of Non-Syndromic Hypodontia with Skeletal Malocclusion in Orthodontic Patients - Faiza Rana, Faiza Malik, Esha Rana, Hana Pervez, Rabia Tabassum, Mehreen Ishtiaq Lone, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hypodontia is one of the frequently observed dental anomalies in which dentofacial esthetics, phonetics, mastication, self-esteem and quality of life can be adversely affected. Awareness of disproportionate tooth number is important and must be considered by orthodontists while making treatment plans to achieve proper occlusion, overbite, and overjet, in order to restrain oral health deterioration. The aim of this study was to determine the frequency of non-syndromic hypodontia in orthodontic patients and its association with skeletal malocclusion. Methods: This retrospective case-series was conducted at the department of Orthodontics, Sharif Medical & Dental College. It involved screening the records of orthodontic patients from last 5 years from October 2017 – October 2021, consisting of standardized good quality orthopantomograms and lateral cephalograms. Patient files with incomplete records, any craniofacial syndrome and/or previous history of tooth loss were excluded. Non-syndromic hypodontia and skeletal malocclusion was recorded along with demographic data, in predesigned proforma. Results: Out of 244 orthodontic patients, 18 patients (7.37%) had non-syndromic hypodontia. Moreover, 63 teeth were missing in 18 patients of NSH. Maxillary arch (52.4%) and upper left quadrant (28.6%) were found to be more frequently affected. The difference of non-syndromic hypodontia among dental arches, quadrants and skeletal malocclusion was statistically significant while for genders it was insignificant. Conclusion: Non-syndromic hypodontia was significantly associated with skeletal malocclusion, highlighting their genetic etiology. Most commonly absent tooth was maxillary lateral incisor followed by mandibular second premolar and lateral incisor.